Analisis Atribut Inovasi dalam Layanan PLN Mobile di Surabaya Utara - Putri, Virania Azzahra; Nawangsari, Ertien Rining (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
PLN Mobile is a digital service innovation developed by PLN in the form of an application with the aim of simplifying electricity services. PLN Mobile was initially launched on October 31, 2016 and then relaunched on December 18, 2020. This study uses a descriptive qualitative research method with a focus on using Rogers (2003) innovation attributes, namely relative advantage, compatibility, complexity, triability and observability. The purpose of this study is to describe and analyze the attributes of innovation in PLN Mobile services in North Surabaya in making it easier for people to accept. Data collection techniques using interviews, observation and documentation. Data analysis uses an interactive model that starts from data collection, data condensation, data display and conclusion drawing/verification. The results of this study indicate that PLN Mobile innovation in the North Surabaya area has a great point of relative advantage, this is indicated by the superiority of PLN Mobile compared to the old service and users benefit from using this innovation. The second has a high level of compatibility to the old procedures, service flow, and in accordance with the needs of PLN customers. The third has a fairly high complexity because it uses technology and is related to internet connectivity to access it. The fourth has the attribute of triability because PLN Mobile has been tested before launching and is actively socialized. The fifth is that PLN Mobile has a great level of observability because every service process can be easily monitored.